In this paper, the differences between the virtual laboratories and the bench laboratory were analyzed and the advantages and disadvantages of the virtual laboratory were established. Search was based on the three laboratory works were developed and carri - Nurgalieva, K.E.; Gavare, Z.; Igenbayeva, A.S.; Kanatova, A.N. (Recent Contributions to Physics, 2019)
In this paper, the differences between the virtual laboratories and the bench laboratory were analyzed and the advantages and disadvantages of the virtual laboratory were established. Search was based on the three laboratory works were developed and carried out through approbation. There were two focus groups of students for analyzing the level of students after their work with the bench and virtual laboratories. As the result the advantages and disadvantages of the virtual laboratory are cleared out. The disadvantage is in having not of opportunity of students to work by hand. Advantages: during work, if the student was unable to complete the work, he can finish it another time. With the help of a virtual program the work is done very quickly. This program does not consume much memory in the computer. Providing the сabinet with bench equipment is more expensive. And the testing shows that if a student additionally works with a virtual program, his level of education increases. Virtual laboratory work are very important and the level of knowledge of students has increased.